Monitoring submicron particles in the atmosphere of a Southeast China city - Jian, Le; Bertolatti, Dean; Zhu, Y.; Zhao, Yun; Shen, F. (The Society of Environmental Toxicology and Chemistry Asia/Parcific Chapter, 2010)
With rapid economic development, the size of the road vehicle fleet has increased dramatically in China. In order to characterise the emission patterns of submicron particulate from on-road vehicles and provide background information for further investigating the health impact from exposure to particles less than/equal to 1.0 μg, a survey was conducted in 2009 in Hangzhou, a Southeast city in China. Autoregressive integrated moving average (ARIMA) analysis was used to model the ultrafine particle (UFP) and particulate matter 1.0 (PM1.0) time series data and explore factors affecting UFP and PM1.0 concentrations. Results showed that the average UFP concentrations were 44.17x103 particle cm-3 -56.45 x103 particle cm-3 and the average concentrations of PM1.0 were 113 μg m-3 - 279 μg m-3 during survey period. UFP and PM1.0 concentrations were higher in the mornings than that in the afternoons.Wind velocity and barometric pressure were inversely correlated with UFP concentration in ARIMA model but the significance of the correlation between UFP and barometric pressure disappeared when the traffic flow was added in the model (p<0.01). Neither wind velocity, barometric pressure nor traffic flow is a significant contributor to UFP emission but environmental factors should be taken into consideration in interpretation of the monitoring results for submicron particles in the atmosphere. This study provides first hand information for future regulations on UFP and PM1.0 and investigations in causal relationship between UFP and PM1.0 from vehicle exhausts and their health effect on humans.